HIGHER ORDER THINKING SKILLS IN MATHEMATICS AT ELEMENTARY SCHOOL - Ndiung, Sabina; Atika, Merlin Titin; Jediut, Mariana; Helmon, Arnoldus (Jurnal Cakrawala Pendas, 2024)
This research aims to describe creative thinking skills and mathematical problem solving abilities through the application of a project-based learning model. This research uses a quantitative approach with a quasi-experimental method with a posttest-only group design. The sample consisted of 53 students in class V of elementary schools in East Manggarai district which consist two class, with details in the experimental class total 27 people and the control class total 26 people. The sampling technique uses random sampling technique. Data collection techniques use test techniques. The tests used are descriptive tests both to measure creative thinking skills and for data about problem solving abilities. Based on the reliability test results, all items are in the high category. The data analysis technique using MANOVA with the help of SPSS 23.00. The asumtion tests used are data normality test, data homogeneity test, and multicolinearity test. Research findings show that both separately and simultaneously the creative thinking ability and problem solving ability of students who receive learning using the project-based learning model is higher than students who receive learning with conventional models. The project model also has a strong and important impact on the creative thinking abilities and mathematical problem solving abilities of elementary school students. In conclusion, the implementation of the project-based learning model is one of the alternative choices used by teachers for creativity in learning mathematics in elementary schools.